Optimized design and test for a pendulum suspension of the crop spray boom in dynamic conditions based on a six DOF motion simulator - Cui, Longfei; Mao, Hanping; Xue, Xinyu; Ding, Suming; Qiao, Baiyu (International Journal of Agricultural and Biological Engineering, 2018)
Spray deposit distribution from a field sprayer is mainly affected by the boom movements when the tractor is driven over a rough soil surface, the pendulum suspension that used to reduce and control the movement of spray boom by isolating the boom from vibrations of the tractor will directly enhance uniform deposition of chemicals. However, how to match the parameters of the suspension with the properties of the boom is the key problem. The dynamic rigid-flexible coupling model of the virtual prototype of the spray boom suspension system was established by using ADAMS and ABAQUS software. An optimization of the suspension parameters for a large spay boom was carried out based on the optimal Latin hypercube design, radial basis function neural network, and multi-objective genetic algorithm NSGA-II. After modified parameters of the suspension, the travel of the sprayer on a typical field motion track was simulated based on a six DOF motion simulator, and the dynamic behavior of the boom suspension was measured. The results show that RMS of the measured boom roll angle and the boom center displacement for optimized solution were reduced by 14.76% and 12.43% compared with the original suspension. Finally, the inertial measurement unit (IMU) was used to measure the movements of the sprayer vehicle during the pesticide application on the Hongze Lake Farm, the experiment of field condition reproduced by using the six DOF motion simulator, the standard deviation of the roll angle and vibration displacement for the optimized sprayer boom are only 0.6382° and 62.279 mm respectively. The research provides theoretical basis and experimental method for parameter optimization of large scale boom suspension. Keywords: boom sprayer, pendulum suspension, parameter optimization, spray boom movement, spray deposit distribution, six DOF motion simulator DOI: 10.25165/j.ijabe.20181103.3717 Citation: Cui L F, Mao H P, Xue X Y, Ding S M, Qiao B Y. Optimized design and test for a pendulum suspension of the crop spray boom in dynamic conditions based on a six DOF motion simulator. Int J Agric & Biol Eng, 2018; 11(3): 76–85.